The transnational in English literature Shakespeare to the modern - Nayar, Pramod K. (Routledge, 2015)
"The Transnational in English Literature examines English literary history through its transnational engagements and argues that every period of English Literature can be examined through its global relations. English identity and nationhood is therefore defined through its negotiation with other regions and cultures. The first book to look at the entirety of English literature through a transnational lens, Pramod Nayar: - Maps the discourses that constitute the global in every age, from the Early Modern to the twentieth century - Offers readings of representative texts in poetry, fiction, essay and drama, covering a variety of genres such as Early Modern tragedy, the adventure novel, the narrative poem, Gothic and utopian fiction - Examines major authors including Shakespeare, Defoe, Behn, Swift, Coleridge, Wordsworth, Austen, Mary Shelley, the Brontes, Doyle, Ballantyne, Orwell, Conrad, Kipling, Forster - Looks at themes such as travel and discovery, exoticism, mercantilism, commodities, the civilisational mission and the multiculturalization of England. Useful for students and academics alike this book offers a comprehensive survey of the English canon questioning and analysing the transnational and global engagements of English literature. Pramod K. Nayar teaches English at the University of Hyderabad, India"--Provided by publisher.